Agreeing to Disagree: The European Union and the United Kingdom after Brexit. (6th September 2020) - Bradley, Kieran
Abstract : Brexit – Withdrawal Agreement – Article 50 TEU – Negotiations – Legal character of agreement – Transition period – 'New legal order' – 'Due regard' – ECJ jurisdiction – Governance – Enforcement and supervision – Dispute settlement – Future relations